Comparison of Asymptomatic Bacteriuria Agents and Antimicrobial Susceptibility in Term and Preterm Pregnancies - Reyhan Ayaz; İhsan Ayhan; Ahmet Naci Emecen; Pinar Ergen; Damla Dökmeci Güney; Özlem Aydın (Düzce Tıp Fakültesi Dergisi, 2022)
Aim: The aim of this study was to compare the resistance to asymptomatic bacteriuria (ABU) between term and preterm pregnancies. Material and Methods: Pregnant women aged 17-41 years who were followed up in the obstetrics department of our hospital and whose urine cultures were sent to the laboratory for analysis and reported as ABU were included in the study. Patients were divided into two groups according to gestational weeks as preterm (<37 weeks) and term (≥37 weeks). The results were compared between the two groups. Results: From among a total of 123 pregnant women, 29 (23.6%) delivered at preterm and 94 (76.4%) at term. The most frequently identified pathogen throughout the study group was 52.0% (n=64) Escherichia coli (E. coli), followed by 16.3% (n=20) Streptococcus agalactiae (S. agalactiae). There was no statistically significant difference in terms of the distribution of E. coli and S. agalactiae between the term and preterm groups (p=0.698 and p=0.930). E. coli was resistant to ampicillin 56.3% (n=36), to cefuroxime 40.6% (n=26). While fosfomycin resistance was 1.6% (n=1), nitrofurantoin resistance was not found. Extended-spectrum beta-lactamase positivity was 23.4% (n=15) in E. coli strains. No statistically significant difference was found in antibiotic resistance rates of E. coli strains between the term and preterm groups. Conclusion: The most commonly isolated pathogen was E. coli which was highly resistant to beta-lactams. Screening of pregnant women for ABU and treatment with appropriate antibiotics; is the most effective way to prevent both maternal and fetal complications and antimicrobial resistance.